2012
DOI: 10.1098/rsif.2012.0470
|View full text |Cite
|
Sign up to set email alerts
|

Physical basis for the adaptive flexibility of Bacillus spore coats

Abstract: Bacillus spores are highly resistant dormant cells formed in response to starvation. The spore is surrounded by a structurally complex protein shell, the coat, which protects the genetic material. In spite of its dormancy, once nutrient is available (or an appropriate physical stimulus is provided) the spore is able to resume metabolic activity and return to vegetative growth, a process requiring the coat to be shed. Spores dynamically expand and contract in response to humidity, demanding that the coat be fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…For example, dormant spores of Bacillus thuringiensis expand and shrink in response to increasing and decreasing relative humidity on different time scales from tens of seconds to minutes (45). The contraction of the coat often is accompanied by the formation of small ridges on the spore surface (46). showed that the surface of Bacillus thuringiensis is covered with crystalline hexagonal honeycomb structures; the surface of Bacillus cereus spores is covered with small randomly oriented domains.…”
mentioning
confidence: 99%
“…For example, dormant spores of Bacillus thuringiensis expand and shrink in response to increasing and decreasing relative humidity on different time scales from tens of seconds to minutes (45). The contraction of the coat often is accompanied by the formation of small ridges on the spore surface (46). showed that the surface of Bacillus thuringiensis is covered with crystalline hexagonal honeycomb structures; the surface of Bacillus cereus spores is covered with small randomly oriented domains.…”
mentioning
confidence: 99%
“…This, in turn, allows a major influx of water into the core, thereby causing it to swell and to rehydrate sufficiently to support metabolism. Concomitantly, the coat (as well as any of the other, more exotic outer layers that are present in many species [5]) is shed by processes that remain poorly understood (7). Disassembly of these layers reveals the germ cell wall, which serves as the cell wall of a newly emerging vegetative cell.…”
mentioning
confidence: 99%
“…However, it is certainly possible that there are changes in the coat associated with germination that facilitate the swelling of spores' outer layers in response to core swelling, and there is a recent report consistent with this idea (29). In addition, whole dormant spores can swell and contract significantly in both the major and minor axes, and this has been suggested to be due at least in part to changes in spore core water content (29,30). It should be noted that the threshold value for ellipse fitting is normalized to 50% of the maximum image intensity that is reduced during germination.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot answer this definitively at present, but it seems most likely that at a minimum it is core swelling that drives this process, since loss of significant amounts of the spore coat by mutation of the major assembly protein CotE has no significant effect on spore wet heat resistance, which is primarily dependent on the core water content (27,28). However, it is certainly possible that there are changes in the coat associated with germination that facilitate the swelling of spores' outer layers in response to core swelling, and there is a recent report consistent with this idea (29). In addition, whole dormant spores can swell and contract significantly in both the major and minor axes, and this has been suggested to be due at least in part to changes in spore core water content (29,30).…”
Section: Discussionmentioning
confidence: 99%